Analisis tentang Lingkungan Pendidikan Formal dalam Pembentukan Perilaku Jujur Siswa di SMKN 1 Bone - Hartinah, Hartinah (Institut Agama Islam Negeri (IAIN) Bone, 2020)
Research discusses the analysis of the Formal education environment in the formation of students ' honest behaviour in SMKN 1 Bone. This research is a type of field research (field reseach) with a qualitative approach, namely research that the procedure produces a descriptive data of written or spoken words from the people and actors that are observed located in SMKN 1 Bone located in Jalan Lapawawoi Karaeng Sigeri, Kelurahan Biru, Sub District Tanete Riattang Bone Regency of South Sulawesi province. The results showed that students ' honest behaviour formation in SMKN 1 Bone are conducted in intra activity in the course and extracurricular activities. To foster and develop these honest characters in their intrurricular activities, educators internalize in the learning process using several methods: Lecture methods, discussion methods, demonstration methods, method of giving assignments, methods of precision and habituation. Analysis of the formal education environment in the establishment of honest behavior of students at SMKN 1 Bone has succeeded. The formal educational environment supports the creation of honest behavior of students in the school environment strongly influenced by; Physical environment, social environment and academic environment.